The Impact of Depot GnRH Agonist on AMH Levels in Healthy Reproductive-Aged Women - Su, H. Irene; Maas, Kevin; Sluss, Patrick M.; Chang, R. Jeffrey; Hall, Janet E.; Joffe, Hadine (The journal of clinical endocrinology and metabolism, 2013)
Context:GnRH agonists (GnRHa) are being used experimentally in an attempt to preserve fertility in young female cancer patients undergoing chemotherapy. Anti-Müllerian hormone (AMH) produced by ovarian granulosa cells may serve as a marker of ovarian reserve, but it is not clear whether this marker is useful during GnRHa treatment.Objective:The purpose of this study was to determine the effect of a depot GnRHa on AMH levels.Design:Depot leuprolide (3.75 mg) was administered in the midluteal phase (MLP) in healthy women. Assessments of AMH, FSH, LH, estradiol, and progesterone were performed in the early follicular phase (EFP) and MLP before GnRHa treatment and approximately 7, 14, and 30 days after GnRHa administration.Setting:The study was conducted in a university research center.Patients:Participants were 33 healthy, premenopausal women aged 18 to 45 years old with regular menses.Results:EFP and MLP AMH levels were similar before GnRHa administration. Relative to MLP AMH levels, AMH decreased 7 days after GnRHa administration by a median of 24% (P < .001) and then increased above pretreatment levels 14 and 30 days after GnRHa by 13% and 32%, respectively (P < .001). Changes in AMH levels did not correlate with changes in gonadotropins, estradiol, or progesterone.Conclusions:Significant changes in AMH levels occur in the first 4 weeks after depot leuprolide administration, suggesting that AMH may not be a reliable marker of ovarian reserve during this interval. Changes in AMH occurred independent of gonadotropin levels, supporting a direct effect of GnRHa on granulosa cell expression of AMH or an indirect effect of GnRHa on the development and/or dynamics of the follicle pool.